About Proper Numbers of Electric Circuit State Matrix - V. S. Safarian (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
An algorithm has been developed to form a matrix for balancing a state of monotonous circuits. It is shown that proper numbers of asymmetric matrix for balancing states of a monotonous circuit are real ones.